Effects of 6-Week Micronutrient Supplementation on Sperm Parameters and Pregnancy Outcomes in Males with Idiopathic Infertility Undergoing Fertility Interventions: A Pilot Cohort Study - Sun, Choo Gim; Da, Aw Lin; Sen, Ooi Bee; Yusof, Zamri; Chan, Huan-Keat; Balanathan, Kathirgamanathan; Zain, Murizah Mohd (Journal of Pharmacy Practice and Community Medicine)
Objective: To evaluate the effectiveness of the consumption of Profortil®, a combination of eight micronutrients, on sperm count, sperm motility, and pregnancy outcomes following a fertility intervention among infertile males in Malaysia. Methods: A cohort study was undertaken at the Seberang Jaya Hospital and the Sultanah Bahiyah Hospital, Malaysia. A total of 90 infertile males were enrolled, 52 of which decided to take two capsules of Profortil® daily for a six-week period during 1st September and 30th November 2016. Those who decided not to consume Profortil® served as the control group (n=38). Semen analysis and an observation of pregnancy outcomes following the fertility interventions were conducted after 6 weeks. Results: Despite the consumption of Profortil®, both groups showed a significant increase in sperm count (p<0.001), but no change in sperm motility after 6 weeks. Although the difference in increment of sperm count between two groups was not significant, more participants who took Profortil® achieved a sperm count above 15 million/mL (25% versus 18.4%). The Profortil® group also demonstrated a higher pregnancy rate following the fertility interventions (26.9% versus 18.4%). Conclusion: The findings suggest that Profortil® could be helpful in improving the sperm parameters and pregnancy outcomes. Nevertheless, to optimize its effectiveness, a longer supplementation duration is likely to be needed.
Keywords: Micronutrient Supplementation; Sperm count; Oligospermia; Male infertility; Pregnancy outcome